Imagining my ideal: a critical case study of digital storytelling as reflective practice. Issue 2 (4th March 2019) - Coggin, Linda Skidmore; Daley, Sharon; Sydnor, Jackie; Davis, Tammi R.
ABSTRACT: Teacher candidates (TCs) must navigate personal, experiential, and theoretical discourses of learning to teach to establish a teaching identity. This article describes a critical case example of digital storytelling to imagine a future classroom. The qualitative research design situates the TCs' digital stories as a performance and analyzes the art form to consider how they might use these texts to imagine and make visible this negotiation. The critical case shows how the TCs used the digital story to make sense of personal experiences, their image of an ideal teacher, methods coursework, and the personal struggle inherent across these sometimes disparate voices of learning to teach. Findings indicate that digital storytelling expands TCs' reflective practice in the supportive environment of a teacher education program.